Cocoa seedlings growth on marginal soil as affected by application of dry walnut leaf compost and arbuscular mycorrhiza fungi - Arum, Ayu Puspita; Fandri, Ferdi Zul; Setiyono, Setiyono; Tanzil, Ahmad Ilham; Saputra, Tri Wahyu (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
Cocoa (Theobroma cacao L.) is a plantation commodity that is widely cultivated in Indonesia, this commodity is very important in Indonesia because it has played a role in the Indonesian economy since 1930. The problem faced in cocoa cultivation is the lack of nutrient availability due to chemicals that cause residue in the soil, resulting in the growth of cocoa seedlings are not optimal, to optimize the growth of cocoa seedlings, provide a mixture of organic fertilizer in the planting medium and provide mycorrhiza. This research used the basic pattern of a factorial Completely Randomized Design (CRD) consisting of 2 factors and repeated 3 times. The first factor is the dose of dry leaf compost (K) which consists of 3 levels, namely: Without dry leaf compost treatment/control (Kâ‚€), dry leaf compost 60 g/polybag (Kâ‚), Dry leaf compost dose 120 g/polybag (Kâ‚‚) and the second factor is the arbuscular mycorrhizal dose (M) which consists of 3 levels, namely: Without arbuscular mycorrhizal fungus treatment/control (Mâ‚€), arbuscular mycorrhizal dose of 15 g/polybag (Mâ‚), and arbuscular mycorrhizal dose of 30 g/polybag (Mâ‚‚) So there are 27 experimental units. The results of the study showed that (1) there was a real interaction between the treatment of compost dose (K) and mycorrhizal dose (M) in safety. The combination of compost dose (K) 120 g/plant and mycorrhiza dose (M) 30 g/plant (K2M2) was the best treatment combination. (2) The treatment of giving a compost dose (K) had a significant effect on the variables of plant height, number of leaves, stem diameter, and plant dry weight. The best treatment was a compost dose of 120g/plant (K2). (3) The mycorrhizal dose (M) treatment had a very significant effect on the variables of plant height, number of leaves, stem diameter, and plant dry weight. The best treatment was a mycorrhizal dose of 30g/plant (M2).